The effect of macroeconomic variables and business environment in Yemen: Role of political stability and economic stability - Musibah, Anwar Salem Omair (2015)
This study was conducted to examine the impact of the foreign direct investment inflows on economic growth in Yemen, and evaluating the role of the moderating effect of political stability and economic stability on the relationships between macroeconomic variables, business environment variables and foreign direct investment inflows. Indeed, the study poses a new stream of research in investigating the effect of political stability and economic stability as moderating variables, recognizing the importance of political stability and economic stability as a critical variable in the course of foreign investment. Thus, the research framework of this study was designed with the integration of New Growth Theory and Firm Theory in tracing the impact of political stability and economic stability on foreign direct investment. This study used annual data for 30 years since the period of 1985 to 2014. The data was collected from the official sources such as Central Bank of Yemen, United Nations Conference on Trade and Development, World Bank and International Monetary Fund. This study used the Augmented Dickey Fuller test to check the stationary of the data and hierarchal regression using STATA statistical software packages. The moderating effects of the determinants political stability and economic stability on the relationships were empirically examined. The findings of this study revealed that gross domestic production growth rate, degree of openness, exchange rate, inflation rate, gross national income, balance of payment, corruption control index, labour cost, infrastructure were significant predictors of foreign direct investment inflows. These findings, therefore, strongly suggested that political stability and economic stability is very important for the country’s domestic and foreign investment in the future course of direction. The study proposed several practical inferences for designing suitable macroeconomic policy and undertaking measures to promote a high economic growth with rising foreign direct investment inflows in the political economy of Yemen